DETERMINATION THINKING SYSTEM AND QUALITY OF MADRASAH EDUCATION: LEADERSHIP ANALYSIS TRANSFORMATIONAL AND TEACHER PROFESSIONALISM (LITERATURE REVIEW OF HUMAN RESOURCE MANAGEMENT) - Yusraini Yusraini; Kemas Imron Rosadi (Dinasti Publisher, 2022)
Research before or Relevant research is very important in something research or article scientific. Research before or relevant research working for strengthen theory and phenomenon connection or influence between variables. this article review Determination Think Madrasah system and Quality: Analysis Leadership Transformational and Professionalism of Teachers, Something Studies Literature Management Resource Human . Destination writing article this To se build hypothesis influence between variable for used in research next. Results from library research this is that: 1) Leadership Transformational take effect to Think System; 2) Influential Teacher Professionalism to Think System; 3) Leadership Transformational take effect to Quality of Madrasah Education; 4) Teacher professionalism is influential to Quality of Madrasah Education; and 5) Thinking System take effect to Madrasah Education Quality